2006
DOI: 10.1186/1471-230x-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium infantisstrains with and without a combination of Oligofructose and Inulin (OFI) attenuate inflammation in DSS-induced colitis in rats

Abstract: Background: Pathogenesis of inflammatory bowel disease is thought to be through different factors and there is a relationship between the gut flora and the risk of its development. Probiotics can manipulate the microflora in chronic inflammation and may be effective in treating inflammation. Bifidobacterium are saccharolytic and their growth in the gut can be promoted by non-absorbable carbohydrates and its increase in the colon appears to be of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
71
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 35 publications
11
71
0
7
Order By: Relevance
“…This effect was counteracted by normalizing the calcium intake of the rats. 68,69 In contrast, Osman et al 70 showed a reduction of bacterial translocation to the liver in a dextran sulfate sodium (DSS)-induced colitis in rats fed oligofructose, whereas bacterial translocation was increased using a combination of oligofructose, inulin, and B. infantis DSM 15158. Mangell et al 71 showed that Lactobacillus plantarum 299v reduced bacterial translocation to liver and mesenteric lymph nodes in rats, whereas prebiotics (oatmeal) did not prevent this.…”
Section: Adverse Effects Of Prebioticsmentioning
confidence: 96%
See 1 more Smart Citation
“…This effect was counteracted by normalizing the calcium intake of the rats. 68,69 In contrast, Osman et al 70 showed a reduction of bacterial translocation to the liver in a dextran sulfate sodium (DSS)-induced colitis in rats fed oligofructose, whereas bacterial translocation was increased using a combination of oligofructose, inulin, and B. infantis DSM 15158. Mangell et al 71 showed that Lactobacillus plantarum 299v reduced bacterial translocation to liver and mesenteric lymph nodes in rats, whereas prebiotics (oatmeal) did not prevent this.…”
Section: Adverse Effects Of Prebioticsmentioning
confidence: 96%
“…OFI alone or the B. infantis strains with and without OFI improved the DSS-induced acute colitis. 70 Two studies using oral administration of lactulose in a DSS rat model (300-1000 mg/kg twice daily) and TNBS rat model showed reduction of colonic inflammation after 6 or 14 days, respectively. This effect was dose-dependent.…”
Section: Dss-induced Colitismentioning
confidence: 99%
“…Moreover the IFN-γ levels were significantly increased in the TNBS model in comparison with other acute and chronic models. Animal models of colitis have been employed to assess the anti-inflammatory effects of plant extracts or their components, polyherbal formulation and probiotics (Jagtap et al 2004;Mahgoub 2003;Osman et al 2006).…”
Section: Inflammation Dth/chs Reaction Carrageenan Paw Oedema Colimentioning
confidence: 99%
“…15 A prebiotic mixture containing inulin and oligofructose administered for 2 weeks showed a 10-fold increase in the number of the bifidobacteria and lactobacilli in human intestine, 16 in addition to their immunomodulatory properties in clinical IBD patient trials 13 and in experimental colitis. 17,18 Inulin alone or in combination with Bifidibacterium infantis strains significantly improved the disease activity indexes and decreased both colonic MPO activity and expression of inflammatory mediators. 19 Lactulose, another synthetic prebiotic, also demonstrated a preventative anti-inflammatory effect in TNBS-induced colitis 5 and IBD patients.…”
Section: Discussionmentioning
confidence: 95%